Organizational Factors for Exploration and Exploitation - Pandey,Sharadindu (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2009)
The Purpose of the paper is to develop a conceptual framework which suggests a relationship between organisational factors and exploratory and exploitative innovation types. We searched major databases like ABI/INFORM global, EBSCO, Elsevier's science direct, Springer link and Emerald full text. Most of studies were included from published sources.We explored the literature of organisational culture, motivational bases of the rewards system and leadership values which are responsible for increasing creative and productive output. Our study has attempted to identify common patterns and themes in the literature regarding the drivers that increase both sides of the organisational creativity. The paper discusses the role of culture, system and styles in the initiation and implementation phases of the innovation called herein exploitative and exploratory innovation.